PERSPECTIVE OF DIRECT LEARNING MODEL - Bobihu, Hazrah; Olii, Rahmat; paputungan, frezy (Indonesian Journal of Social Science and Education (IJOSSE), 2025)
Efforts to improve the quality of human resources are carried out through learning activities. The learning that is expected is learning that can explore self-potential so that quality improvement can be realized. In learning there are learning models and methods. In this study, the learning carried out applies the direct learning model and the Kumon method. This descriptive study aims to describe the management of learning carried out by teachers in implementing direct learning models with the Kumon method, student activities during the learning process, student learning outcomes after the learning is implemented and student responses to learning and carried out at SMAN-1 Krian with the subjects of the study being students of class XI IPA 6 and mathematics teachers of class XI IPA 6. The results of the study are that the management of learning carried out by teachers is included in the good criteria, namely with a score of 3.03, student activities that are desired during the learning process other than irrelevant activities appear with a percentage of 90.09% with the dominant activity being listening / paying attention to the teacher's explanation, student learning outcomes in this study are out of 34 students, 31 students completed and 3 students did not complete. Classically, students completed with a percentage of 91.18%, the students' response to this learning was positive, namely out of 34 students, 75% expressed a positive response to the learning.